Effect of silicification on the water sorption properties of microcrystalline cellulose II (2011)
ABSTRACT: The aim of this study was to investigate the water sorption behavior of cellulose II:SiO2 composites and to determine the influence of silicification on this property. These composites were prepared by spray-drying at a cellulose II:SiO2 ratio of 98:2, 95:5, 90:10 and 80:20. The nonlinear models of Guggenheim-Andersonde Boer (GAB), Generalized D’Arcy and Watt (GDW) and Hailwood & Horrobin (HH), were used for the characterization and analysis of the isotherms. The infrared and powder X-rays characterization showed no signs of chemical modification or change in the polymorphic form of cellulose II by SiO2. The parameters derived from these models indicated that only a 20% level of silicification was able to hinder the water sorption properties of cellulose. Silicon dioxide was the most hydrophobic material since it had a lower ability to form hydrogen bonds with water than cellulose II. This finding was reflected in a delayed compact disintegration time when high levels of silicification (20%) and compression pressures higher than 120 MPa were used.